Highly Cited Research on Medicinal Plants from India: A Scientometric Insight into Trends, Impact, and Influence - Chaman Sab, M; Mueen Ahamed, K.K; Bagalkoti, Vitthal (Information Research Communications, 2024)
Aim and Background The present study examines the Scientometric Insight into Trends, Impact, and Influence of Highly Cited Research on Medicinal Plants from India. Materials and Methods The study retrieved and identified highly cited papers related to India’s scientometric research from the Web of Science citation database using a predefined search strategy covering 2021-2024. For each downloaded record, the data elements included publication type, citation count, author count, institutional affiliations, country or origin, and funding sources. Microsoft Excel was then used to analyze the data and examine collaborative connections among organizations, authors, and keywords. 4,396 were recognized from India. Results Among these 59 were HCPs received 1065 to 100 citations, collectively received. The citation range of these HCPs is as follows 59 papers. This comprehensive bibliometric analysis provides an in-depth and enlightening overview of significant articles, journals, authors, institutions, and themes in the field. Conclusion Through this overview by utilizing these valuable insights, researchers can swiftly grasp the present state, focal points, and emerging patterns of bibliometric research in India during the thought the last five years. To improve the future, the community should strive to foster interdisciplinary and international cooperation among Indian scholars and organizations.
Keywords: Medicinal Plants; Highly cited; Web of Science; Research Trends; India